The impact of marketing capabilities on agile marketing (Entrepreneurship Journal for Finance and Business, 2024)
The study aims to know the relationship between the independent variable represented by marketing capabilities and their dimensions (market sensing capabilities, marketing learning capabilities, market targeting capabilities) with the dependent variable, which is agile marketing and its sub-dimensions (reducing excessive marketing operations, reducing surplus inventory for marketing operations, reducing inappropriate transportation). It is necessary to reduce excessive processing steps, reduce defective outputs in marketing, and reduce waiting times. The sample of the study was (50) male and female employees at various levels and administrative responsibilities specialized in providing oil products at the Vegetable Oil Factory, which is one of the important companies in Iraq that seeks to provide its products to customers in a way that exceeds competing companies. The research problem is represented by the limited interest in the Vegetable Oil Factory in Baghdad for marketing. Agile in his marketing work through the optimal use of marketing capabilities. And its lack of readiness for change in order to adopt the modern marketing philosophy to enhance its goals and marketing performance in the Iraqi business environment, in addition to the presence of many wasted money, effort, time and resources during the company’s marketing operations. To achieve the objectives of the study, a model was formulated for the study consisting of two main variables, and two main hypotheses were derived, the first related to correlation and the other to influence. The most important conclusion reached is that there is an acceptable presence of marketing capabilities in the vegetable oil factory that helps in achieving lean marketing.